Mapping a Legal Study on Cybersecurity and Data Protection: A Bibliometric Review and Its Implications for Regulation in the Digital Age - Judijanto, Loso; Lubis , Arief Fahmi; Padlilah, Padlilah (West Science Law and Human Rights, 2025)
This study provides a bibliometric review of the current research landscape on cybersecurity and data protection, focusing on the evolving technological advancements and regulatory responses in the digital age. By analyzing literature from Scopus, this review maps key themes and emerging trends in the field, including the integration of machine learning, blockchain, and the Internet of Things (IoT) in cybersecurity practices. The study highlights the growing emphasis on data privacy, particularly in sectors like healthcare, and the increasing importance of privacy-by-design principles. The review also identifies gaps in existing regulatory frameworks, emphasizing the need for global cooperation and adaptive legal structures to address the dynamic nature of cyber threats and data protection challenges. The findings suggest that future research should focus on the intersection of emerging technologies and legal frameworks to ensure comprehensive, forward-thinking approaches to cybersecurity and data protection.